STUDI PEMBERDAYAAN MASYARAKAT DESA DALAM UPAYA MENINGKATKAN KESEJAHTERAAN DI DESA POLOKARTO KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - Suminah Suminah (AGRITEXTS: Journal of Agricultural Extension, 2007)
Famer community's understanding to problems faced and their resources will become promoter in their effort to exit from poorness and improve life prosperity. This research aim to improve the awareness of village community to know their problems faced, resources potential had, and formulate the resolving alternative to their problems. In this research, data is in qualitative character. Data obtained through partisipative approach with the PRA (Participatory Rural Appraisal) method. Data analysis was done by logical framework to compiled plan of village community activities.